2015
DOI: 10.1111/jcpp.12389
|View full text |Cite
|
Sign up to set email alerts
|

The intergenerational impact of war: longitudinal relationships between caregiver and child mental health in postconflict Sierra Leone

Abstract: The findings highlight an important interplay between caregiver and child mental health within the postconflict setting and the need for psychosocial interventions to extend beyond the individual to account for family dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(75 citation statements)
references
References 56 publications
4
68
1
2
Order By: Relevance
“…It has been suggested that children may be both directly affected by war exposure, and indirectly affected as a result of the impact of war exposure on their mothers' psychological functioning (Betancourt et al 2015;Chemtob et al 2010;Smith et al 2001). For example, in Bosnian school aged children, both the extent of exposure to war and mothers' emotional distress were associated with children's emotional distress following the Bosnian war (Smith et al 2001).…”
Section: War Exposure and Child Adjustmentmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been suggested that children may be both directly affected by war exposure, and indirectly affected as a result of the impact of war exposure on their mothers' psychological functioning (Betancourt et al 2015;Chemtob et al 2010;Smith et al 2001). For example, in Bosnian school aged children, both the extent of exposure to war and mothers' emotional distress were associated with children's emotional distress following the Bosnian war (Smith et al 2001).…”
Section: War Exposure and Child Adjustmentmentioning
confidence: 97%
“…Studies from diverse cultures in different war contexts, have documented the adverse effect of exposure to war on children's adjustment (Betancourt et al 2015;Chemtob et al 2010;Feldman and Vengrober 2011;Feldman et al 2013;Masten and Narayan 2012;Panter-Brick et al 2014;Smith et al 2001). It has been suggested that children may be both directly affected by war exposure, and indirectly affected as a result of the impact of war exposure on their mothers' psychological functioning (Betancourt et al 2015;Chemtob et al 2010;Smith et al 2001).…”
Section: War Exposure and Child Adjustmentmentioning
confidence: 97%
“…The model has originally been developed in contexts of family violence and has proven to be valuable for understanding continuity in offending. Since recently, the cycle of violence theory is receiving increasing attention in conflict-affected contexts [19][20][21][22][23][24][26][27][28][29], perhaps because rates of relapse into conflict are worrying [1]. Overall, insight into the mechanisms fostering intergenerational continuity is still limited, however.…”
Section: Discussionmentioning
confidence: 99%
“…In conflict-affected countries, substantial higher levels of domestic or familial violence often occur [45,46]. In this regard, research in contexts marred by chronic violence-in Western and non-Western settings-has shown that family dynamics and caregiving may impact children's functioning and their role in reproducing violence [28,[47][48][49]. Together with other risk factors or vulnerabilities at different system levels, compromised caregiving may contribute to putting society at risk for new episodes of violence or conflict [22,24,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation